Application of microscope‐based scanning software (Panoptiq) for the interpretation of cervicovaginal cytology specimens. Issue 12 (28th September 2017) - Groen, Ruben; Abe, Kuniko; Yoon, Han‐Seung; Li, Zaibo; Shen, Rulong; Yoshikawa, Akira; Nitanda, Takao; Shimizu, Yukiko; Otsuka, Isao; Fukuoka, Junya
Abstract : BACKGROUND: Digital pathology increasingly has been gaining the attention of pathologists worldwide. However, the application of digital cytology by Panoptiq (ViewsIQ, Vancouver, Canada) microscope‐based scanning software is relatively unexplored. Panoptiq enables the operator to combine low‐power panoramic digital images with z‐stacks at regions of interest with a significantly smaller image size than that obtained by whole‐slide scanning. The current study aimed to evaluate the feasibility of the use of Panoptiq in the digital interpretation of cervicovaginal cytology specimens in comparison with conventional light microscopy. METHODS: A total of 100 liquid‐based cytology slides were selected sequentially. The dotted slides were reviewed and scanned, in which all dotted areas were scanned further by the ×20 objective with z‐stacks. The cases were reviewed by 4 pathologists and a cytotechnologist using conventional light microscopy and digital cytology images acquired by Panoptiq and interpreted based on the Bethesda classification system. The washout time was set as 3 weeks. The Cohen kappa coefficient was calculated to measure the agreement between the 2 modalities. RESULTS: Digital cytology demonstrated an intermodality agreement among 3 observers who had sufficient training in digital pathology at concordance rates between 81% and 90% with kappa values between 0.76 and 0.86, whereas the other 2 observers who did not have sufficient training in digital pathology had lower agreement at a concordance rate of between 56% and 57%, with kappa values between 0.41 and 0.44. CONCLUSIONS: Panoptiq appears to be feasible for the interpretation of cervicovaginal cytology specimens but requires adequate training in digital pathology. Cancer Cytopathol 2017;125:918‐25. © 2017 American Cancer Society. Abstract : The development of a robust digital device for cytology is critical for the advancement of the field. The Panoptiq imaging system is feasible for cervicovaginal cytology specimens when performing continuous quality controls.